The Jingshan Report Opening China's Financial Sector - China Finance 40 Forum Research Group (ANU Press, 2020)
The Jingshan Report is a collection of research papers on key issues for China's financial opening, including reform of the RMB exchange rate regime, management of cross-border capital flows and financial support for the Belt and Road Initiative. Authored by leading experts in the relevant fields, the report examines the evolution, current status and problems with the financial opening policy over the past four decades, and puts forward policy recommendations on how to steadily push forward China's financial opening.